Microstructures and mechanical properties of grey irons by adding high-content steel scrap. (1st November 2016) - Li, P.; Wang, J. J.; Ge, D. C.; Sui, G. H.; Chen, G. H.; Yang, G. W.; Wang, D. S.; Tang, B.; Tang, W. M.
Abstract : The grey irons prepared by adding steel scrap as main raw material were designed. Effect of the steel scrap content on the microstructures, mechanical properties and fracture mechanisms of the HT250 grey irons was studied. The results show that as the steel scrap content increased, the microstructures of the grey irons are improved, and the mechanical properties of the grey irons are therefore increased. The grey iron by adding 100 wt-% steel scrap has the optimal microstructure composed of the small and curved graphite flakes, the refined pearlite colonies and the dispersed MnS and TiN inclusions, also, it has the highest mechanical properties and comprehensive performance.